Importance of red patches diagnosed in cystoscopy for haematuria and lower urinary tract symptoms. Issue 975 (31st January 2007) - Fernando, Herman; Thota, Sreenivasa S; Burtt, Glyn; Waterfall, Nicholas; Husain, Imtiaz
Abstract : Background: Biopsy of the red patches in the bladder, when found at cystoscopy, is routinely performed in urological practice. This is done to establish the sinister diagnosis of carcinoma-in-situ among other causes. Objective: To analyse the pathology of the red patches and to determine if routine biopsy of these patches is warranted. Patients and methods: This was a retrospective study conducted over a period of 36 months, in which 50 patients were identified, who underwent biopsies of their red patches. All patients with a history of bladder carcinoma and obvious bladder tumours were excluded from this study. Results: The mean age of the patients was 60.8 years. 25 patients had cystoscopy for lower urinary tract symptoms, 21 for haematuria and 4 for recurrent urinary tract infection. Carcinoma in situ was found in 4 (8%) patients, of whom only 2 had positive urine cytology. Conclusion: It is prudent to perform a biopsy of all incidentally diagnosed red patches because of a major yield rate of carcinoma in situ. This procedure also picks up other important pathologies, which help in further management.